Синтез і структура порожнинних наносфер діоксиду титану - Gorbik, P. P.; Dubrovin, I. V.; Demchenko, Ju. O.; Kashin, G. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
Hard hollow spherical nanoparticles of titanium dioxide have been fabricated by hydrolysis of titanium tetrachloride on the surface of aerosol droplets in the atmosphere of water or ammonia vapor. The aerosol droplets were obtained by ultrasonic dispersion of a solution of titanium tetrachloride in an inert hydrophobic solvent. The composition and structure of the synthesized hollow nanospheres of titanium dioxide were determined by electron microscopy, TDA, X-ray analysis and Auger-electron spectroscopy.